Oral delivery of bi-autoantigens by bacterium-like particles (BLPs) against autoimmune diabetes in NOD mice. (31st December 2023) - Mao, Ruifeng; Wang, Jin; Xu, Ying; Wang, Yuqi; Wu, Mengmeng; Mao, Lixia; Chen, Yingying; Li, Dengchao; Zhang, Tong; Diao, Enjie; Chi, Zhenjing; Wang, Yefu; et al.
Abstract: Induction of oral tolerance by vaccination with type 1 diabetes mellitus (T1DM)-associated autoantigens exhibits great potential in preventing and treating this autoimmune disease. However, antigen degradation in the gastrointestinal tract (GIT) limits the delivery efficiency of oral antigens. Previously, bacterium-like particles (BLPs) have been used to deliver a single-chain insulin (SCI-59) analog (BLPs-SCI-59) or the intracellular domain of insulinoma-associated protein 2 (IA-2ic) (BLPs-IA-2ic). Both monovalent BLPs vaccines can suppress T1DM in NOD mice by stimulating the corresponding antigen-specific oral tolerance, respectively. Here, we constructed two bivalent BLPs vaccines which simultaneously deliver SCI-59 and IA-2ic (Bivalent vaccine-mix or Bivalent vaccine-SA), and evaluated whether there is an additive beneficial effect on tolerance induction and suppression of T1DM by treatment with BLPs-delivered bi-autoantigens. Compared to the monovalent BLPs vaccines, oral administration of the Bivalent vaccine-mix could significantly reduce morbidity and mortality in T1DM. Treatment with the bivalent BLPs vaccines (especially Bivalent vaccine-mix) endowed the mice with a stronger ability to regulate blood glucose and protect the integrity and function of pancreatic islets than the monovalent BLPs vaccines treatment. This additive effect of BLPs-delivered bi-autoantigens on T1DM prevention may be related to that SCI-59- and IA-2-specific Th2-like immune responses could be induced, which was more beneficial for the correction of Th1/Th2 imbalance. In addition, more CD4 + CD25 + Foxp3 + regulatory T cells (Tregs) were induced by treatment with the bivalent BLPs vaccines than did the monovalent BLPs vaccines. Therefore, multiple autoantigens delivered by BLPs maybe a promising strategy to prevent T1DM by efficiently inducing antigen-specific immune tolerance.